Analisis Sistem Informasi Menajemen Terhadap Pengambilan Keputusan Pada Kantor Wilayah Badan Pertanahan Sumatera Utara - Arfan Tanjung; Mawaddah Irham (FEB Universitas Maritim Semarang, 2024)
This research aims to analyze the role of the Management Information System (SIM) in supporting the decision-making process at the North Sumatra Land Agency Regional Office. This study explores the integration, reliability and contribution of information systems used in managing property and land information and their impact on the efficiency and effectiveness of decisions. The research methodology includes surveys of system users, interviews with top-level managers, and documentation of analyzes related to the technological infrastructure implemented. The data collected was analyzed using qualitative methods to understand the adequacy of the system, its suitability to user needs, and its contribution to the decision-making process. The research results show that the implemented Management Information System has a number of advantages, including efficient data management, better information accessibility, and real-time data availability. However, challenges such as data security and the need for increased integration with other systems were identified as potential improvements. In the context of decision making, MIS is proven to play an important role in providing timely and accurate information for management in making strategic decisions regarding land ownership, document updates and property transfers. Recommendations are prepared based on research results to improve the efficiency and effectiveness of the Management Information System to support better decision making at the North Sumatra Land Agency Regional Office. This research provides valuable insights for managers and developers of information systems in the context of the Land Agency, as well as a basis for improving the system to increase its decision-making role to a more strategic and responsive nature.